PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN INFORMATIKA DI UPTD SMPN 11 BARRU - Nasir; Atul Azizah, Fitri; Nurwandayani; Ismail, Lukman; Sahira, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine the effect of the Snowball Throwing learning model on the cognitive learning outcomes of students of Innformatics class VII.3 UPTD SMPN 11 Barru. This research design uses a one group pretest posttest design. Class VII.3 UPTD SMPN 11 Barru became the sample in this study. Data collection was done through a multiple choice question test totaling 10 items for each pretest and posttest test. Test the data of students' cognitive learning outcomes using normal distribution of one sample shapiro-wilk and homogeneity. The results showed a correlation sign of 0.000 <0.05 and in the paired sample t test data the sign value was 0.000 <0.05. Based on this, the value between the pretest and postest there is an influence or relationship to the provision of treatment, so that the snowball throwing learning model as a treatment in learning affects the cognitive learning outcomes of informatics students in class VII.3 UPTD SMPN 11 Barru.